Effect of low-dose lidocaine on MEPs in patients undergoing intracranial tumor resection with propofol anesthesia: A randomized controlled trial. Issue 32 (12th August 2022) - Liu, Meijuan; Wang, Ning; Wang, Dong; Liu, Juan; Zhou, Xuelong; Jin, Wenjie
Abstract : Objective: To investigate the effect of low-dose lidocaine on motor evoked potentials (MEPs) in patients undergoing intracranial tumor resection with propofol anesthesia. Methods: Forty patients who underwent intracranial tumor resection and required MEP monitoring were selected. They were randomly divided into the lidocaine group (group L, n = 20) and the control group (group C, n = 20) by computer-generated randomization. All patients were given propofol anesthesia under the guidance of the bispectral index. In group L, 1 mg/kg of lidocaine was injected intravenously during anesthesia induction. Then, lidocaine was continuously pumped at a speed of 1 mg/kg/h until the operation started. Group C was given an equal volume of normal saline. Heart rate (HR), mean artery pressure (MAP), and bispectral index were recorded before anesthesia induction (T0), 2 minutes after tracheal intubation (T1), and 35 minutes (T2), and 50 minutes (T3) after anesthesia induction. The amplitude and latency of MEP at T2 and T3, the total dosage of propofol after anesthesia induction, and adverse events before T3 were recorded. Results: Compared with those in group C, HR and MAP were significantly decreased at T1 in group L. No significant differences were observed in HR and MAP at T0, T2, and T3 between group L and group C. The total dosage of propofol and the incidence of adverse events were significantly lower in group L than in group C before T3. There were no significant differences in the amplitude and latency of MEP between the 2 groups at each time point. Conclusions: Low-dose lidocaine has no obvious effect on MEP in patients undergoing intracranial tumor resection. However, it increased hemodynamic stability, reduced propofol use, and decreased the incidence of adverse events.